Розробка методів адаптації дизелів до біонафтових паливних композицій - Лєвтєров, А.М.; Савицький, В.Д.; Гладкова, Н.Ю. (Проблемы машиностроения, 2017)
Запропоновано теоретично обґрунтований метод компенсування втрат ефективної потужності дизеля внаслідок переходу на живлення біонафтовими паливними композиціями. Експериментально доведено, що підвищення потужності біодизельного двигуна до рівня базового дизеля супроводжується погіршенням екологічних показників, які все ж залишаються кращими за аналогічні показники дизельного прототипу. Проведено експериментальну перевірку визначених аналітично заходів зі зниження вмісту оксидів азоту та твердих частинок у відпрацьованих газах дизеля, що працює на сумішевому біонафтовому паливі. Предложен теоретически обоснованный метод компенсирования потерь эффективной мощности дизеля вследствие перехода на питание бионефтяными топливными композициями. Экспериментально доказано, что увеличение мощности биодизельного двигателя до уровня базового дизеля сопровождается ухудшением экологических показателей, преимущества которых перед аналогичными показателями дизельного прототипа все-таки сохранятся. Проведена экспериментальная проверка определенных аналитически мероприятий по снижению содержания оксидов азота и твердых частиц в отработавших газах дизеля, работающего на смесевом бионефтяном топливе. Many publications have shown that, with some degradation of a diesel engine's power and economic performance, using fuel compositions containing vegetable oil ethers significantly reduces the toxicity of engine exhaust gases. Our experimental research into the motor qualities of mixture fuel have shown that increasing the volume share of the biological component of binary fuel slowly degrades the energy indicators of a diesel engine and improves its ecological features. In so doing, engine exhaust gases toxicity is not reduced drastically. The main goal of the research effort was increasing the energy and ecological indicators of a biodiesel engine by improving the methods of its adaptation to biodiesel fuel compositions. The task of the investigation was a comprehensive experimental validation of such methods. A theoretically substantiated method of compensating for diesel effective power losses was suggested by changing to fuel mixture supply. The method consists in increasing the energy content of engine cylinders by increasing the maximum fuel injection rate. Experiments have proved that increasing biodiesel engine power does not degrade ecological indicators considerably. These indicators are better than similar ones of a diesel prototype as to the level of emission of exhaust gases (EG) for carbon oxide and carbon dioxide by 36% and 11%, respectively; for nitrogen oxides, by 18%; for unburned carbon, by 7 times, and for EG smoke opacity, by 28%. Analysis of publications and preliminary estimates and experiments have defined actions to be taken to reduce the content of nitrogen oxides and solid particles in the exhaust gases of a diesel engine running on mixture fuel. The actions are to shorten fuel injection advance and use lean fuel-and-air mixtures. Experiments have shown that optimising the fuel injection advance angle and the minimal value of the air ratio improves dramatically (up to 50-80%) the ecological performance of a biodiesel engine. The new methods of improving the energy and ecological indicators of a biodiesel engine have confirmed experimentally their high effectiveness. Besides, these methods have a regulating character, making their implementation easier and cheaper.